The godfather. Part III [videorecording (Blu-Ray)] - Garcia, Andy; Coppola, Francis Ford, 1939-; Puzo, Mario, 1920-1999; Pacino, Al, 1940-; Keaton, Diane (Paramount, 2017)
Don Corleone decides to buy his salvation by investing in the Catholic Church, which he finds to be a more corrupt brotherhood than his own.